The Implementation of Salam-Contract For Agriculture Financing Through Islamic-Corporate Social Responsibility (Case Study of Paddy Farmers in Tuban Regency Indonesia) - Hudaifah, Ahmad; Tutuko, Bambang; Sawarjuwono, Tjiptohadi (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
This research is aimed at discovering a stable financial scheming formula or model that would be compatible with the natural characteristics of a paddy farming cycle in Tuban. The qualitative research employs the use of an active participatory community through the means of a focus group discussion, an in-depth interview and face to face interviews with respective stakeholders and key informants. The Salam contract, which is highly beneficial is a prospective f inancial scheme that terminates the long business chain found in most businesses in Indonesia. The Corporate Social Responsibility which is managed through the Syariah approach (I-CSR) from a company, can become the solution to bridge the gap found in the implementation of funds for a Salam contract. The Salam contract applicability is dependent on the Islamic farmer cooperatives (BMT), a unit of joint venture organization serving as the key players in the execution of the function of a paddy warehouse-trading agent and direct financing to farmers. Strong support also comes from the zakat, infāq, and shodaqoh institution (LAZ) whose role is educating and encouraging the paddy farmers’ skills and competency, especially to enable them access end-user markets using the aid of information technology Abstrak:Penelitian ini bertujuan untuk menemukan formula skema pembiayaan pertanian yang stabil sesuai karakteristik dengan alamah pertanian padi di Kabupaten Tuban. Metode penelitian kualitatif digunakan dalam menyelesaikan penelitian ini dengan partisipasi komunitas aktif melalui media diskusi kelompok, wawancara mendalam tatap muka dan observasi kepada informan kunci dan pihak yang terlibat secara langsung dalam tata niaga pertanian padi di Kabupaten Tuban. Kontrak salam adalah skema pembiayaan yang sangat menguntungkan bagi petani dan pada penerapannya mampu mengambil pembiayaan peran distributor dalam tata niaga pertanian padi. Islamic Corporate Social Responsibility (I-CSR) yang dikelola berdasarkan ekonomi syariah dari perusahaan yang beroperasi di prinsip wilayah Tuban bisa menjadi solusi dana yang dikembangkan untuk pembiayaan pertanian yang dihindari oleh perbankan karena siklus bisnis yang berbeda. Keberlangsungan kontrak salam pertanian untuk komoditas padi akan bergantung pada koperasi petani yang terdiri dari koperasi simpan pinjam Syariah (BMT), gudang padi, penggilingan padi dan unit perdagangan yang kesemuanya disebut sebagai KUB (Kelompok Usaha Bersama). Dukungan yang kuat juga berasal dari Lembaga zakat, infāq dan shodaqoh, yang memiliki peran untuk melakukan pelatihan keahlian petani dan membantu memenuhi kebutuhan dasar petani yang menjadi anggota dalam KUB.